2022
DOI: 10.3390/electronics11101657
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Jerk Optimal Preview Control Strategy to Enhance Performance of Active and Semi-Active Suspension Systems

Abstract: This study aims to demonstrate how to compute the damping coefficient of a continuously variable damper for semi-active preview control suspensions while considering the sprung-mass jerk and the controller’s performance advantage. Optimal control theory is used to derive and validate the proposed preview approach to future road disturbances. Despite reduced body acceleration, semi-active suspensions with preview control display an increase in body jerk, implying that ride comfort may not be improved in practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Hence, such significant improvements in ride quality can be achievable at the penalty of vehicle handling. In [ 42 ], using a semi-active suspension system, we have implemented a preview-based anti-jerk control strategy to improve ride comfort without degrading the road-holding capability under different road conditions. Despite the exciting results, to the researcher’s knowledge, the previous anti-jerk methodologies only focus on enhancing ride comfort using conventional active or semi-active suspension systems.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, such significant improvements in ride quality can be achievable at the penalty of vehicle handling. In [ 42 ], using a semi-active suspension system, we have implemented a preview-based anti-jerk control strategy to improve ride comfort without degrading the road-holding capability under different road conditions. Despite the exciting results, to the researcher’s knowledge, the previous anti-jerk methodologies only focus on enhancing ride comfort using conventional active or semi-active suspension systems.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the spring mass acceleration (SMA) of MFRR is much smaller than that of the passive suspension system (PS) and FPID on single-bump and sine wave roads, and the control system exhibits good control performance. Youn [12] controlled the root mean square of acceleration of 1/4 suspension through road prediction simulation and optimal control theory. Time domain simulation shows that the preview control strategy can effectively reduce suspension vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Young I. [29] et al designed an anti-jerk optimal predictive control method for active and semi-active suspension systems. This approach can reduce body jerk and improve ride comfort.…”
Section: Introductionmentioning
confidence: 99%